Application of the Maximum 1/3 Obligatory Bequest (Wasiat wajibah) Principle in Adopted Children Grants - Kusuma Arum, Nimas Ayuni; Sanjaya, Umar Haris (Jurnal Hukum Replik, 2024)
This research focuses on explaining about grants to adopted children that exceed 1/3 of the assets of their adoptive parents, resulting in heirs being hindered from obtaining their inheritance. This research using contxt of probles as how is the application of the maximum one-third provision on grants to adopted children? What are the consequences if the assets granted to the adopted child exceed one-third of the assets of the adoptive parents? This study falls under the typology of normative legal research. The research findings explain that grants to adopted children must adhere to the maximum one-third provision of the assets owned by the grantor, as stipulated in Article 210 of the Compilation of Islamic Law (KHI). If this provision is not followed by the grantor, a violation occurs in the grant process, potentially causing harm to the heirs. As a result of assets exceeding the maximum 1/3 provision, the grant can still be valid or null and void under the law.